The bHLH Transcription Factors TSAR1 and TSAR2 Regulate Triterpene Saponin Biosynthesis in Medicago truncatula. Issue 1 (23rd November 2015) - Mertens, Jan; Pollier, Jacob; Vanden Bossche, Robin; Lopez-Vidriero, Irene; Franco-Zorrilla, José Manuel; Goossens, Alain
Abstract : Basic helix-loop-helix family transcription factors from subclade IVa specifically regulate the biosynthesis of the triterpene saponins in a model legume. Abstract: Plants respond to stresses by producing a broad spectrum of bioactive specialized metabolites. Hormonal elicitors, such as jasmonates, trigger a complex signaling circuit leading to the concerted activation of specific metabolic pathways. However, for many specialized metabolic pathways, the transcription factors involved remain unknown. Here, we report on two homologous jasmonate-inducible transcription factors of the basic helix-loop-helix family, TRITERPENE SAPONIN BIOSYNTHESIS ACTIVATING REGULATOR1 (TSAR1) and TSAR2, which direct triterpene saponin biosynthesis in Medicago truncatula . TSAR1 and TSAR2 are coregulated with and transactivate the genes encoding 3-HYDROXY-3-METHYLGLUTARYL-COENZYME A REDUCTASE1 (HMGR1) and MAKIBISHI1, the rate-limiting enzyme for triterpene biosynthesis and an E3 ubiquitin ligase that controls HMGR1 levels, respectively. Transactivation is mediated by direct binding of TSARs to the N-box in the promoter of HMGR1. In transient expression assays in tobacco ( Nicotiana tabacum ) protoplasts, TSAR1 and TSAR2 exhibit different patterns of transactivation of downstream triterpene saponin biosynthetic genes, hinting at distinct functionalities within the regulation of the pathway. Correspondingly, overexpression of TSAR1 or TSAR2 in M. truncatula hairy roots resulted in elevated transcript levels of known triterpene saponin biosynthetic genes and strongly increased the accumulation of triterpene saponins. TSAR2 overexpression specifically boosted hemolytic saponin biosynthesis, whereas TSAR1 overexpression primarily stimulated nonhemolytic soyasaponin biosynthesis. Both TSARs also activated all genes of the precursor mevalonate pathway but did not affect sterol biosynthetic genes, pointing to their specific role as regulators of specialized triterpene metabolism in M. truncatula .